LEGISLATION, IDEAS AND PRE-SCHOOL EDUCATION POLICY IN THE TWENTIETH CENTURY: FROM TARGETED NURSERY EDUCATION TO UNIVERSAL EARLY CHILDHOOD EDUCATION AND CARE. Issue 5 (2nd September 2020) - West, Anne
ABSTRACT: This paper explores legislative provision and pre-school education policy in England over the course of the twentieth century. The paper argues that there has been a significant ideational shift over this period, from a policy focus on nursery education for poor children to universal early childhood education. Not only have ideas changed but provision and funding have changed. Although there have been major revisions to legislative provision, there are elements of continuity as regards the institutions delivering early childhood education, particularly maintained nursery schools and nursery classes, but with layering of private-for-profit and not-for-profit institutions to 'fill the gap' in provision. At the same time, the central state has taken increasing control of publicly funded early childhood education through legislative provision.